The Correlation Between Students’ Reading Habit and Their Reading Comprehension in Analytical Exposition Texts of Eleventh Grade at SMA PGRI Pekanbaru (Lembaga Pengembangan Kinerja Dosen, 2025)
This research focuses on the correlation between students’ reading habit and their reading comprehension in analytical exposition texts of eleventh grade students at SMA PGRI Pekanbaru. This research was motivated by the fact that some students face difficulties in reading English texts due to a lack of reading habit and challenges in understanding English texts, especially analytical exposition texts. This research employed a correlational design. The sample consisted of 37 eleventh grade students of SMA PGRI Pekanbaru in the academic year 2024/2025, selected through total sampling technique. To collect the data, the researcher used a questionnaire to measure students’ reading habit and an objective test to assess their comprehension of analytical exposition texts. Pearson Product-Moment correlation analysis showed a correlation coefficient (r_xy) of 0.501, indicating a moderate positive correlation between the two variables. With a significance value of 0.001, which is lower than 0.05, the correlation was statistically significant. Furthermore, since the r_value (0.501) was greater than the r_table value (0.344) for 37 respondents at the 5% significance level, the alternative hypothesis (Ha) was accepted. These findings indicate that students with better reading habits tend to have higher comprehension in understanding analytical exposition texts.